Air-processable high-efficiency CISSe solar cells from DMF molecular solution and their application to perovskite/CISSe tandems. Issue 4 (13th January 2022) - Siddique, Yasir; Son, Kyungnan; Rana, Tanka Raj; Naqvi, Syed Dildar Haider; Hoang, Pham Minh; Ullah, Asmat; Tran, Huyen; Lee, Sang Min; Hong, Sungjun; Ahn, Seung Kyu; Jeong, Inyoung; Ahn, SeJin
Abstract : A simple, air processable, DMF molecular ink-based process is presented through which it was able to achieve a new certified record efficiency of 14.4% for the low-gap CuIn(S, Se)2 device. Abstract : A breakthrough in the N, N -dimethylformamide (DMF) molecular ink route for fabricating highly efficient, low bandgap CuIn(S, Se)2 (CISSe) solar cells is presented, demonstrating a newly certified record efficiency of 14.4% from air-processed devices. This finding changes the previous recognition of the requirement of a controlled environment, i.e., a nitrogen-filled glovebox, to obtain a high efficiency via this route. Instead, it is determined that DMF ink can be processed in air under certain optimized conditions without sacrificing the device performance, which opens a new horizon in terms of commercialization while maintaining all the potential benefits of solution-based routes. In particular, the air annealing temperature after spin-coating the ink is found to be a critical parameter in controlling the electrical properties of the absorber films. Air annealing not only facilitates carbon removal but also influences the crystallinity of the precursor films, which further determines the diffusion behavior of the constituent metal atoms during high-temperature selenization, ultimately affecting the interfacial recombination and carrier transport characteristics of devices. Our CISSe devices processed in air at an optimized air annealing temperature are further combined with semitransparent perovskite devices to realize all-solution-processed 4-terminal (4T) perovskite/CISSe tandem solar cells, demonstrating a promising efficiency of 23.03%, which is also the highest efficiency for all-solution-based perovskite/CISSe tandem configurations.